Undetected Multidrug-Resistant Tuberculosis Amplified by First-line Therapy in Mixed Infection - Hingley-Wilson, Suzanne M. (Centers for Disease Control and Prevention, 2013)
Infections with >1 Mycobacterium tuberculosis strain(s) are underrecognized. We show, in vitro and in vivo, how first-line treatment conferred a competitive growth advantage to amplify a multidrug-resistant M. tuberculosis strain in a patient with mixed infection. Diagnostic techniques that identify mixed tubercle bacilli populations are needed to curb the spread of multidrug resistance.